Corporate groups and shadow business practices / Linn Anker-Sørensen. - Anker-Sørensen, Linn, 1985- (Cambridge University Press, 2022)
The uniqueness of this book is its conceptualization of a corporate group as a system of interaction, comprised of nodes, links and internal governance tools. This framework can be used to understand what constitutes a group, based on affiliation-linkages. By increasing our perception of group-structuring we can assess the extent to which existing laws address all variables. If the law does not consider certain variables to be used for identifying groups, a case of shadow business may be identified. Group-transparency is a recurring topic on the regulatory agenda. In this book, three legal domains are analysed questioning whether specific amendments have led to increased group-transparency: the control-definition for consolidated accounts, shareholder-transparency in company law, and major holding disclosure in listed companies. This book identifies deficiencies of the law in obtaining its regulatory objective of group-transparency, and proposes an interpretative solution based on Systems Thinking.